2001
DOI: 10.1074/jbc.m103782200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Endothelial Cell Apoptosis by High Density Lipoproteins (HDL) and HDL-associated Lysosphingolipids

Abstract: Apoptotic cell death following injury of vascular endothelium is assumed to play an important role in the pathogenesis of atherosclerosis. In this report, we demonstrate that high density lipoproteins (HDL), a major anti-atherogenic lipoprotein fraction, protect endothelial cells against growth factor deprivation-induced apoptosis. HDL blocked the mitochondrial pathway of apoptosis by inhibiting dissipation of mitochondrial potential (⌬ m ), generation of reactive oxygen species, and release of cytochrome c in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
251
1
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(270 citation statements)
references
References 46 publications
11
251
1
7
Order By: Relevance
“…SDS-PAGE and Western Blotting-SDS-PAGE and Western blotting were performed exactly as described previously (14). For each blot with anti-phosphospecific antibodies loading controls were performed using an antibody against a ubiquitously expressed protein (␣-actin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SDS-PAGE and Western Blotting-SDS-PAGE and Western blotting were performed exactly as described previously (14). For each blot with anti-phosphospecific antibodies loading controls were performed using an antibody against a ubiquitously expressed protein (␣-actin).…”
Section: Methodsmentioning
confidence: 99%
“…HDL was shown previously to induce a variety of cellular signals, none of which, with the exception of protein kinase C, could be unequivocally shown to be associated with removal of cellular cholesterol (8 -16). Moreover, most of these responses could not be mimicked by apoA-I, thus precluding their direct involvement in the specific cholesterol efflux (11,14,16). The goal of the present study was to specifically investigate the apoA-I-induced signal transduction and its relationship to cholesterol efflux.…”
mentioning
confidence: 99%
“…HUVECs undergo apoptosis upon serum deprivation, and previous studies have shown that isolated human HDL, but not low density lipoprotein, inhibits serum starvation-induced endothelial cell apoptosis (40). In cells that were serum-deprived for 6 h, the level of apoptosis as measured by both annexin staining ( Fig.…”
Section: Hdl Oxidative Modification By (Patho)physiologically Relevanmentioning
confidence: 99%
“…In the endocrine pancreas, Akt1 has been shown to regulate ␤-cell growth and survival (21). In endothelial cells, Akt is a mediator of the antiapoptotic effects of HDL (22).…”
Section: Effects Of Lipoproteins On Cell Proliferation Cyclin B1mentioning
confidence: 99%